Posttraumatic Stress and Posttraumatic Stress Disorder after Termination of Pregnancy and Reproductive Loss: A Systematic Review. (5th February 2015) - Daugirdaitė, Viltė; van den Akker, Olga; Purewal, Satvinder
Abstract : Objective . The aims of this systematic review were to integrate the research on posttraumatic stress (PTS) and posttraumatic stress disorder (PTSD) after termination of pregnancy (TOP), miscarriage, perinatal death, stillbirth, neonatal death, and failed in vitro fertilisation (IVF). Methods . Electronic databases (AMED, British Nursing Index, CINAHL, MEDLINE, SPORTDiscus, PsycINFO, PubMEd, ScienceDirect) were searched for articles using PRISMA guidelines. Results . Data from 48 studies were included. Quality of the research was generally good. PTS/PTSD has been investigated in TOP and miscarriage more than perinatal loss, stillbirth, and neonatal death. In all reproductive losses and TOPs, the prevalence of PTS was greater than PTSD, both decreased over time, and longer gestational age is associated with higher levels of PTS/PTSD. Women have generally reported more PTS or PTSD than men. Sociodemographic characteristics (e.g., younger age, lower education, and history of previous traumas or mental health problems) and psychsocial factors influence PTS and PTSD after TOP and reproductive loss. Conclusions . This systematic review is the first to investigate PTS/PTSD after reproductive loss. Patients with advanced pregnancies, a history of previous traumas, mental health problems, and adverse psychosocial profiles should be considered as high risk for developing PTS or PTSD following reproductive loss.